Factors associated with early hospital readmission for acute decompensation of cirrhosis - prospective cohort study - Tamara Liana Zocche; Cláudia Maccali; Fernanda Cristina de Augustinho; Elayne Cristina de Morais Rateke; Camila Matiollo; Ariane Borgonovo Rayes; Dariana Carla Maggi; Esther Buzaglo Dantas-Corrêa; Leonardo de Lucca Schiavon; Janaina Luz Narciso-Schiavon (ABCS Health Sciences)
Introduction: The first months after the hospitalization of cirrhotic patients are considered at high risk for new complications. Knowing the factors associated with early readmission in these individuals may contribute to the development of preventive strategies that avoid the risks and costs related to a new hospitalization. Objective: To investigate the factors associated with the early readmission of hospitalized patients due to acute decompensation of cirrhosis. Methods: Data from the first hospitalization of each patient was considered during the study period and were followed up to the 90th day by telephone contact. A prospective cohort study in Southern Brazil. Results: Between 2011 and 2016, 280 patients were included in the study. The mean age was 55.68±11.21 years, and 71.8% were males with a mean MELD of 15.65±5.64 and 41.4% Child-Pugh C. Early readmission occurred in 91 cases (32.5%). In the logistic regression analysis, CLIF-SOFA variables (odds ratio [OR] 1.137, 95% confidence interval [CI] 1.003–1.289, p=0.045) and several complications present in the initial hospitalization (OR 1.503, 95% CI 1.074–2.105, p=0.018) independent of early readmission. Early readmission rates were 16.8% in patients with CLIF-SOFA <8 and less than 2 complications at admission and 49.2% in those with CLIF-SOFA ≥8 and 2 or more complications at the initial hospitalization. Conclusion: Simple parameters such as CLIF-SOFA and the number of complications of cirrhosis present at hospital admission are predictors of early readmission and can be used as tools to individualize the follow-up of cirrhotic patients after hospital discharge.